Influence of nickel on secondary hardening of a modified AISI H13 hot work die steel. Issue 2 (15th February 2019) - Xia, S.W.; Zuo, P.; Zeng, Y.; Wu, X.
Abstract: This paper focuses on the effects of nickel on secondary hardening of a modified H13 hot work die steel. Both the non‐nickel steel and the nickel‐added steel get a secondary hardening peak at 520 °C, and the secondary hardening peak trends to increase in the nickel‐added steel. On the basis of scanning electron microscope and transmission electron microscope observation, the rise of the secondary hardening peak is in connection with the precipitation of M3 C type carbides. More strip‐shaped and needle‐shaped M3 C type carbides precipitated from matrix. By means of internal friction, the result suggests that nickel does not affect the position of the Snoek‐Kê‐Köster peak, but the height of Snoek‐Kê‐Köster peak of the nickel‐added steel is higher, which indicates nickel enhances the interaction between dislocations and interstitial atoms, promoting the precipitation of carbides.